The Impact of Post-traumatic Stress of SARS-CoV-2 Affliction on Psychological and Mental Health of Student Survivors: Cross Sectional Study - Dixit, Snehil; Musa, Alamin; Sillva, Audrey Borghi; Reddy, Ravi Shankar; Abohashrh, Mohammed; Kakaraparthi, Venkata Nagaraj; Asiri, Faisal; Caruso, Flavia Rossi; Govindappa, Shashi Kumar; Mohammed, Arif Ahmad (Frontiers in Public Health, 2022)
Background COVID-19 survivor's population is often associated with a long term impact on mental and psychological health. Recent included studies have also stated affliction of mental health due to fear of virus and preventive policies among the college students. Objectives The research was conducted to find the psychological and mental impacts of SARS-CoV-2 affliction among the students' survivors in the university. Methods The study design of the experiment was cross-sectional, sampling technique was non probability and sampling method being applied was convenience sampling. IBM Statistical Package for the Social Sciences version 20 was used for analyses. Descriptive data was examined and results were showed as mean and standard deviations, percentages, frequencies for continuous variables of IES-R scale (Intrusion, Avoidance, and Hyperarousal) using the total sample of n = 34. Results Out of 34 only 24 student survivors responded to the online survey post COVID-19 recovery, with an overall participation level of 71%. Grading was given for the total IES-R score which was subdivided into a predefined range. Out of 24 participants, 9 (38%) participants showed the symptoms of mild (n = 2)–severe (n = 7) psychological impacts. On correlation of factors total IES-R score and taste and sense of smell were moderately correlated. The ordinal regression for complete loss of sense of taste and smell was also significant. Conclusion The results from IES-R evaluation clearly outlines the presence of psychological sequels post recovery of COVID-19 episodes among the young college survivors. Complete loss of sense of smell and taste may be an indicator of psychological sequelae as compared to reduce sense of smell.